Improvement of Airflow Distribution in a Glutinous Rice Cracker Drying Cabinet - Pakamon Pintana (2018)
© 2017 The Authors. Published by Elsevier Ltd. Fried glutinous rice cracker or Khaotan is one of the important traditional snacks for local Thai economy. When there is no sunlight, a dryer is usually employed in moisture removal process of Khaotan products. A traditional dryer is essentially a drying cabinet with multidirectional flow of hot flue gas from liquefied petroleum gas burner. In this work, an improved design using biomass energy with recirculation of unidirectional airflow inside the drying cabinet was developed. For this improved design of Khaotan dryer, airflow distribution was crucial in providing uniform drying condition and ensuring that all rice crackers were uniformly dried. Numerical simulation based on solving Navier-Stokes equations was carried out to predict airflows in the improved dryer. Swing panel was used to vary the direction of bulk air flow. Effects of swing angle (30, 45, and 60°) and air velocity (0.5, 1, 1.5 m/s) were investigated. Good airflow distributions without dead zone can be obtained from the simulation and implemented in experimental runs. Flow trajectories in the drying cabinet were found to give good agreement between prediction and experiments. With improved design and installation of swing panel, the times used to reduce the Khaotan moisture content to 10% dry basis and the operating cost in this process were reduced, hence, better energy efficiency.